1971
DOI: 10.1063/1.1659999
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Deformation in Central Regions of Epitaxial Silicon Slices

Abstract: Central yielding, as well as peripheral slip, was observed in curved epitaxial silicon slices produced in the laboratory. The central plastic deformation is the result of compressive stresses set up by the entrapment of a hot central region within a colder annular zone. A stress analysis was performed which explains the occurrence and relative intensities of slip in the two regions by reference to the distortion energy densities throughout the slice. A model of the centrally localized plastic deformation in {H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1973
1973
2003
2003

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…164,167 This was interpreted as a result of the entrapment of a hot region within a colder annular zone in a concave shaped wafer. 164,167,194 Further examination of the front-and back-surface of the wafer indicated that dislocations moved out of the wafer and preferentially piled up on the front ͑i.e., concave͒ shaped wafer surface or near the periphery area due to its larger ͑compressive͒ stress compared to the convex surface. 164,167,194 This observation was clarified via a detailed study of the warpage of silicon wafers, induced by oxygen precipitation in wafers processed in furnaces, without the complication of a back-surface epitaxial susceptor contact.…”
Section: Wafer Mechanicsmentioning
confidence: 99%
See 4 more Smart Citations
“…164,167 This was interpreted as a result of the entrapment of a hot region within a colder annular zone in a concave shaped wafer. 164,167,194 Further examination of the front-and back-surface of the wafer indicated that dislocations moved out of the wafer and preferentially piled up on the front ͑i.e., concave͒ shaped wafer surface or near the periphery area due to its larger ͑compressive͒ stress compared to the convex surface. 164,167,194 This observation was clarified via a detailed study of the warpage of silicon wafers, induced by oxygen precipitation in wafers processed in furnaces, without the complication of a back-surface epitaxial susceptor contact.…”
Section: Wafer Mechanicsmentioning
confidence: 99%
“…14͒ and their colleagues. 164,167 Excessive oxygen precipitation can also preclude effective lithographic printing due to uncontrolled wafer warpage as shown by Hirofumi Shimizu and colleagues. 168,169 The increased ultilization of rapid thermal annealing ͑RTA͒ requires attentiveness to minimize global alignment errors as well as to monitor warpage so as to minimize global alignment errors in lithography.…”
mentioning
confidence: 99%
See 3 more Smart Citations